Consistent response of weeds according to Grime's CSR strategies along disturbance and resource gradients in Bordeaux vineyards. (22nd August 2022) - Fried, Guillaume; Blanchet, Cécile; Cazenave, Loreleï; Bopp, Marie‐Charlotte; Kazakou, Elena; Metay, Aurélie; Christen, Maxime; Alard, Didier; Cordeau, Stéphane
Abstract: Vineyards are an appropriate model for testing the filtering effect of management practices on weed communities, as a wide range of practices (tillage, herbicides and mowing) is implemented. The aim of this study is to highlight which trait values are selected by each practice in different environmental conditions, with special references to Grime's CSR strategies. A combination of a multivariate analysis (RLQ) and the fourth‐corner analysis was used to analyse 400 floristic samples belonging to 100 vineyards in the wine‐growing region of Bordeaux (France). The main structure of vineyard weed communities was shaped by the opposition between mowing, favouring hemicryptophytes with a competitive strategy, and soil tillage, favouring therophytes and nutrient‐demanding species with a ruderal strategy. Secondly, the vineyard weed communities differed according to the trophic status of the soil. Vineyards on acidic, sandy soils with low organic matter were characterised by small‐seeded annuals with a stress‐tolerant strategy whereas vineyards with clayey, calcareous soils rich in organic matter, harboured larger perennial nitrophilous species with large seeds and a competitive strategy. Our study is the first to show that weed species responded consistently to two independent gradients with specific traits associated with disturbance (life cycle and SLA) and soil resources (plant height and seed mass) gradients. Based on knowledge of the soil characteristics, it becomes possible to predict which type of weeds will develop according to the combination of practices applied on the vineyard rows and inter‐rows.